Targeted Delivery of Self-Complementary Adeno-Associated Virus Serotype 9 to the Brain, Using Magnetic Resonance Imaging-Guided Focused Ultrasound - Thévenot, Emmanuel (Mary Ann Liebert, Inc., 2012)
Noninvasive drug delivery to the brain remains a major challenge for the treatment of neurological disorders. Transcranial focused ultrasound combined with lipid-coated gas microspheres injected into the bloodstream has been shown to increase the permeability of the blood–brain barrier locally and transiently. Coupled with magnetic resonance imaging, ultrasound can be guided to allow therapeutics administered in the blood to reach brain regions of interest. Using this approach, we perform gene transfer from the blood to specific regions of the mouse brain. Focused ultrasound was targeted to the right hemisphere, at multiple foci, or restricted to one focal point of the hippocampus or the striatum. Doses from 5×10(8) to 1.25×10(10) vector genomes per gram (VG/g) of self-complementary adeno-associated virus serotype 9 carrying the green fluorescent protein were injected into the tail vein. A dose of 2.5×10(9) VG/g was optimal to express the transgene, 12 days later, in neurons, astrocytes, and oligodendrocytes in brain regions targeted with ultrasound, while minimizing the infection of peripheral organs. In the hippocampus and striatum, predominantly neurons and astrocytes were infected, respectively. Transcranial focused ultrasound applications could fulfill a long-term goal of gene therapy: delivering vectors to diseased brain areas directly from the circulation, in a noninvasive manner.